1994
DOI: 10.1210/en.135.1.431
|View full text |Cite
|
Sign up to set email alerts
|

A novel cell layer without corticosteroid-synthesizing enzymes in rat adrenal cortex: histochemical detection and possible physiological role

Abstract: A stratum of cells that did not contain both aldosterone synthase cytochrome P450 (cytochrome P450aldo) and cytochrome P45011 beta was found immunohistochemically between the zona glomerulosa and the zona fasciculata of the rat adrenal cortex. As cytochromes P450aldo and P45011 beta are the enzymes responsible for the biosynthesis of aldosterone and corticosterone, respectively, the cells there are considered to be incapable of synthesizing both aldosterone and corticosterone. Furthermore, the cells are regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
55
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 0 publications
6
55
0
Order By: Relevance
“…Bertholet 1980, Zajicek et al 1986. A functional transition zone has been described in the rat adrenal gland in which cells differ both morphologically and physiologically from either zona fasciculata or zona glomerulosa cell type (Mitani et al 1994). Certainly, if such a migration does occur a transition zone should exist in which both, or neither, zona glomerulosa and zona fasciculata type cells would be found.…”
Section: Discussionmentioning
confidence: 99%
“…Bertholet 1980, Zajicek et al 1986. A functional transition zone has been described in the rat adrenal gland in which cells differ both morphologically and physiologically from either zona fasciculata or zona glomerulosa cell type (Mitani et al 1994). Certainly, if such a migration does occur a transition zone should exist in which both, or neither, zona glomerulosa and zona fasciculata type cells would be found.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that for functional purposes, zonation of the rat adrenal cortex can be separated into the ZG and ZF/ZR. This differentiation is associated with the exclusive presence of aldosterone synthase (CYP11B2) in the glomerulosa whereas 11β-hydroxylase (CYP11B1) is exclusively present in the rat ZF/ZR (Ogishima et al 1992;Mitani et al 1994). Enzymes that catalyze those steroidogenic pathways are biochemically essential to partitioning mineralocorticoid-active steroids of the glomerulosa from the glucocorticoid-producing steroids of the inner zones (Vinson 2003).…”
Section: A B C D E Fmentioning
confidence: 99%
“…Although the GH-receptor was present throughout the adrenocortical region, as seen in the foetal adrenal, a relatively higher level of gene and protein expression was confined to a distinct region at the interface of the zona glomerulosa and zona fasciculata. Studies in the adult rat have identified a novel cell layer devoid of both mineralocorticoid-and glucocorticoid-synthesizing enzymes between the zona glomerulosa and zona fasciculata, which is believed to be the progenitor cell zone of the rat adrenal cortex (Mitani et al 1994). A thin layer of cells (which may be analogous to the progenitor zone of the rat adrenal) has also been identified between the zona glomerulosa and zona fasciculata of the adult sheep adrenal cortex (McDougall et al 1980), the so called 'intermediate cells' of this zone possessing unique cellular morphology intermediate between typical zona glomerulosa and zona fasciculata cells.…”
Section: Discussionmentioning
confidence: 99%